Genetic Distinctiveness of Rye In situ Accessions from Portugal Unveils a New Hotspot of Unexplored Genetic Resources - Monteiro, Filipa; Vidigal, Patrícia; Barros, André B.; Monteiro, Ana; Oliveira, Hugo R.; Viegas, Wanda (Frontiers in Plant Science, 2016)
Rye (Secale cereale L.) is a cereal crop of major importance in many parts of Europe and rye breeders are presently very concerned with the restrict pool of rye genetic resources available. Such narrowing of rye genetic diversity results from the presence of ‘Petkus’ pool in most modern rye varieties as well as ‘Petkus’ x ‘Carsten’ heterotic pool in hybrid rye breeding programs. Previous studies on rye’s genetic diversity revealed moreover a common genetic background on landraces (ex situ) and cultivars, regardless of breeding level or geographical origin. Thus evaluation of in situ populations is of utmost importance to unveil “on farm” diversity, which is largely undervalued. Here, we perform the first comprehensive assessment of rye’s genetic diversity and population structuring using cultivars, ex situ landraces along a comprehensive sampling of in situ accessions from Portugal, through a molecular-directed analysis using SSRs markers. Rye genetic diversity and population structure analysis does not present any geographical trend but disclosed marked differences between genetic backgrounds of in situ accessions and those of cultivars/ex situ collections. Such genetic distinctiveness of in situ accessions highlights their unexplored potential as new genetic resources, which can be used to boost rye breeding strategies and the production of new varieties. Overall, our study successfully demonstrates the high prospective impact of comparing genetic diversity and structure of cultivars, ex situ and in situ samples in ascertaining the status of plant genetic resources.